(untitled) (Jagannath University Journal of Life and Earth Sciences, 2025)
This paper aims to analyze the livelihood status of the urban poor in Dhaka city. A total of 120 households from one urban poor or slum settlements were surveyed. Based on participants’ responses in the study area, we utilized a Likert scale from 0 to 1. This scale was subsequently classified into different categories based on the specific dimension being assessed. The study revealed different levels of livelihood capital in the poor households, which reflected their overall livelihood status. The findings indicated a challenging situation for slum dwellers. Although the human capital score was relatively good compared to other capitals, there were lack of formal education and training opportunities. Financial capital was notably in poor condition, with very low income, expenditures, savings, and limited asset ownership. While housing structures in the slum were good, insufficient sanitation and water supply facilities led to a moderate physical capital status. Social capital was characterized by strong community relationships but limited organizational participation, resulting in a moderate status. Overall, the livelihood status of the slum dwellers was moderate. The findings recommend that greater importance should be given to improving capitals to enhance the adaptive capacity of the urban poor households to reduce their poverty and to cope with periods of crises. Jagannath University Journal of Life and Earth Sciences, 10 (2): 195-210 (December 2024)